Exploiting embedded sensing in outdoor localization : a data-driven perspective - Wang, Jin (2019)
Although research community have put lots of effort in improving localization in indoor environment through various of sensing techniques, outdoor localization still heavily relies on GPS solely. Despite GPS performs successfully in perfect outdoor scenario (e.g., large open air zone), many other outdoor scenarios in metropolitan area make GPS fail to achieve a satisfactory performance due to signal blocking or multi-path effect. Therefore, to improve localization performance in metropolitan area, an integrated outdoor localization solution is desired, which takes GPS as one part and other sources as supplementary. For designing such an integrated solution, we need to consider two questions: (1) what are the proper supplementary sources? (2) when are the proper moments to trigger a switch between GPS and other sources?